2013
DOI: 10.1021/cg401455c
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-Supramolecular Structures by Self-Assembly through Weak Interactions in Mixed Ligand Metal Complexes of Adenine and Malonate

Abstract: The reactions of sodium malonate with Co II , Cu II , or Zn II salts in the presence of adenine afforded the compounds [Co(7H-ade-N9) 2 (H(3), all of which have been characterized by elemental analyses, mass spectrometry, FT-IR, electronic and EPR spectroscopy, magnetic measurements, and single-crystal X-ray diffraction. Complex 1 is an ion-pair product managed by charge-assisted noncovalent interactions. Complex 2 is formed by binuclear [Cu(mal)(Hade)(H 2 O)] 2 units bridged by malonate ligands, and 1D coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Malonate has been extensively studied regarding its role as a magnetic-exchange passageway in Cu(II) complexes, polynuclear compounds and coordination polymers [36][37][38]. In most cases, malonato ligand promotes ferromagnetic coupling.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Malonate has been extensively studied regarding its role as a magnetic-exchange passageway in Cu(II) complexes, polynuclear compounds and coordination polymers [36][37][38]. In most cases, malonato ligand promotes ferromagnetic coupling.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…In most cases, malonato ligand promotes ferromagnetic coupling. In previous studies about the magnetostructural correlations of malonato-based Cu(II) complexes and extended systems [37][38][39][40], it was concluded that the parameter that rules, primarily, the magnetic interaction between metal ions is the relative position of the carboxylato bridge of the malonate ligand related to the Cu(II) ions: equatorial-equatorial (strong interaction), equatorial-apical (weak interaction) and apical-apical (negligible interaction). According to their supramolecular structures, 1, 2, and 3 form chains with a regular alternation of the corresponding complex units, which are linked as a bidentate (η 5 -chelation) + monodentate (1), bidentate (η 5 -chelation) + mono-dentate (2), bidentate (η 5 -chelation) + bis(monodentate) (3) ligand through two carboxylate oxygens of the malonate, via hydrogen-bonding interactions, with the antisyn coordination mode (figures 2, 4, and 5), which correspond to the equatorial-apical carboxylate bridge in the solid-state supramolecular structures.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…It also has been demonstrated that some CPs are capable of adsorbing and entrapping a broad range of molecules, due to their good biocompatibility and porosity [34,39]. Adenine, as an important naturally occurring nitrogen heterocycle present in nucleic acids [40], has multiple possible metal-binding modes [41][42][43]. It has been reported that adenine could coordinate with Zn [44], Au [45], Ag [46], Co [47] or Cu [48] to form CPs with diversified morphology and structure.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used approach for engineering the crystal structure of such complexes employ non-covalent intermolecular forces (hydrogen bonding, aromatic ring stacking, etc.) [11,12]. However, although there have been many reports on supramolecular systems, it still remains a difficult job to explore several complexes with different topological networks.…”
Section: Introductionmentioning
confidence: 99%